CMT 2019
DOI: 10.24983/scitemed.cmt.2019.00106
|View full text |Cite
|
Sign up to set email alerts
|

Updates on the Management of Epistaxis

Abstract: Epistaxis (i.e., nosebleed) is a common otolaryngologic emergency; however, it is seldom life-threatening and most minor nosebleeds stop on their own or under primary care from medical staff. Nonetheless, cases of recurrent epistaxis should be checked by an otolaryngologist, and severe nosebleeds should be referred to the emergency department to avoid adverse consequences, including hypovolemic shock or death. This paper reviews current advances in our understanding of epistaxis as well as updated treatment al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
(115 reference statements)
0
8
0
2
Order By: Relevance
“…Posterior epistaxis arises from damage to posterior nasal septal artery. 6 In a study by Shah et al anterior epistaxis was more common (69.29%) than posterior type (21.05%). 12 Pandey et al in their study also observed that anterior nasal bleed occurred in 37 of 42 cases.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Posterior epistaxis arises from damage to posterior nasal septal artery. 6 In a study by Shah et al anterior epistaxis was more common (69.29%) than posterior type (21.05%). 12 Pandey et al in their study also observed that anterior nasal bleed occurred in 37 of 42 cases.…”
Section: Discussionmentioning
confidence: 93%
“…Epistaxis is estimated to occur in 60% of population worldwide during their lifetime and about 6% of those with nose bleeds seek medical treatment. 6 The present hospital based observational study was thus planned to observe the clinical profile of patients with epistaxis, its varied etiologies and management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epistaxis is expected to affect sixty per cent of people globally at some point in their lives, and only about six per cent of those who experience nasal bleeding take medical assistance. 3,4 Children with <10 years of age show an increased prevalence, which further again increases after thirty-five years. 4,5 In general, males are affected slightly more compared to females until fifty years of age, ABSTRACT Background: Epistaxis (nose-bleed) is one of the commonest emergencies presenting to an otolaryngological emergency that affects up to sixty per cent of the population in their lifetime; in this, six per cent needs medical care.…”
mentioning
confidence: 99%